2010
DOI: 10.4194/trjfas.2010.0401
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In this study, changes in chemical and sensorial quality of hot smoked Atlantic bonito (Sarda sarda, Bloch, 1838) during the storage at 4±1°C and 17±3°C were investigated. In addition, biochemical composition and yield after processing were determined. The values for moisture, crude protein, crude fat, ash and salt were found as 67.71, 14.55, 12.87, 1.76 and 0.70% for fresh bonito, while 57.13, 20.55, 13.97, 3.69 and 3.33% for smoked bonito, respectively. The yield after smoking was calculated as 78.02%. Tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…In this study, the proximate composition of Atlantic bluefin tuna (T. thynnus) was determined as moisture (63.9%), total lipid (10.7%), crude protein (21.9%), and ash (2.1%) which is in accordance with previous research that indicated that the proximate composition of farmed and wild Atlantic bluefin tuna consisted of the following: lipid rate (11.04–12.85%), protein rate (20.96–21.09%) and moisture rate (61.03–63.28%) [ 26 ]. The proximal values of Atlantic bonito were determined as: protein (14.3%), fat (17.8%), moisture (68.2%), and ash (1.8%) ( Table 1 ), which were in agreement with results reported by Koral et al [ 38 ] who indicated the protein, lipid and moisture levels as 14.55, 12.87 and 67.71%, respectively. As one of the most commonly used freshwater fish species, a wide range of research conducted on the proximate composition of trout varies depending on feeding, season, and gender.…”
Section: Resultssupporting
confidence: 89%
“…In this study, the proximate composition of Atlantic bluefin tuna (T. thynnus) was determined as moisture (63.9%), total lipid (10.7%), crude protein (21.9%), and ash (2.1%) which is in accordance with previous research that indicated that the proximate composition of farmed and wild Atlantic bluefin tuna consisted of the following: lipid rate (11.04–12.85%), protein rate (20.96–21.09%) and moisture rate (61.03–63.28%) [ 26 ]. The proximal values of Atlantic bonito were determined as: protein (14.3%), fat (17.8%), moisture (68.2%), and ash (1.8%) ( Table 1 ), which were in agreement with results reported by Koral et al [ 38 ] who indicated the protein, lipid and moisture levels as 14.55, 12.87 and 67.71%, respectively. As one of the most commonly used freshwater fish species, a wide range of research conducted on the proximate composition of trout varies depending on feeding, season, and gender.…”
Section: Resultssupporting
confidence: 89%
“…Modified atmosphere packaging (MAP) and vacuum packaging (VP), along with cold temperature, have been found as enhanced preservation techniques. MAP and VP systems could provide improved seafood shelf life and suitable organoleptic quality (Koral, Sevim, & Bekir, 2010). However, packaging without oxygen may result in fat oxidative spoilage as well as improved organoleptic properties in fish (Jeveheri Baboli, Velayat Zadeh, Jagher, & Pashaei, 2016).…”
Section: Introductionmentioning
confidence: 99%